VD_FINDINFO Arrêt / 2017 / 833 vom 28. März 2018 - VD Tribunal cantonal (2018)
TENUE DU MÉNAGE, MÉTHODE MIXTE D'ÉVALUATION, DEGRÉ DE L'INVALIDITÉ | 28a al. 1 LAI, 28a al. 2 LAI, 28a al. 3 LAI, 25 al. 1 let. b RAI